2020
DOI: 10.22207/jpam.14.3.21
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling of Class I Integron Gene in MDR Salmonella typhi Isolates

Abstract: Typhoid fever is a paramount reason for horribleness that more mortal sin “around the sum ages aggregations clinched alongside iraq it initiated by salmonella typhi. Salmonella typhi is diagnosed serologically by the Widal test and confirmed by vitek and using polymerase chain reaction (PCR) based amplification of DNA from the bacterial samples of typhoid fever patients. The present study was designed to detect class I integron gene encoding antimicrobial of S. typhi using appropriate primers by PCR. These iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
1
1
Order By: Relevance
“…In the current study, only 32(13%) positive blood cultures identified as S.typhi depend on colony morphology on culture medium, biochemical testing, and the automated GN Vitek-2 system. Compared to our study, hospitals in Najaf, Iraq, reported a higher rate of culture-positive typhoid fever cases in 2017 and 2020 (29,30). The high prevalence of the S.typhi strain in Iraq and other Middle Eastern countries is consistent with data stating that 80 % of S.typhi -infected patients originate from the Asian continent, while the remainder is primarily from Africa and Latin America (31).…”
Section: Out Of 246 Blood Specimens Collected From a Patient With Sus...supporting
confidence: 89%
“…In the current study, only 32(13%) positive blood cultures identified as S.typhi depend on colony morphology on culture medium, biochemical testing, and the automated GN Vitek-2 system. Compared to our study, hospitals in Najaf, Iraq, reported a higher rate of culture-positive typhoid fever cases in 2017 and 2020 (29,30). The high prevalence of the S.typhi strain in Iraq and other Middle Eastern countries is consistent with data stating that 80 % of S.typhi -infected patients originate from the Asian continent, while the remainder is primarily from Africa and Latin America (31).…”
Section: Out Of 246 Blood Specimens Collected From a Patient With Sus...supporting
confidence: 89%
“…"This study used 150 stool samples collected from patients with suspected typhoid fever to isolate and diagnose S.typhi. In the current study, only 13(8.7%) positive samples identified as S.typhi based on colony morphology on culture medium, biochemical testing amongst others, This is lower than reports from a study of hospitals in Najaf, Iraq, where a higher rate of culture-positive typhoid fever isolates was reported in 2017 and 2020" [19,20].…”
Section: Molecular Detection Of Plasmid Mediated Quinolone Resistant ...contrasting
confidence: 84%
“… Forest plot showing the pooled prevalence of gyrA gene in resistant S. Typhi isolates estimated by a random effect model of meta-analysis. (91.3%, I 2 : 93.99, 95% CI: 84.1–95.5, p -value < 0.001) [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. …”
Section: Figurementioning
confidence: 99%